Biology and Mass Rearing Studies of Eucanthecona furcellata Wolf. (HEMIPTERA: PENTATOMIDAE) a Potential Polyphagous Predator and its Effect on Field Population of White Slug Caterpillar, Parasa philepida in Cabadbaran, Agusan del Norte, Philippines - Vivencio C. Gallego; Ruby T. Escalona; Joana M.S. Ferreira (International Coconut Community Journal, 1993)
The biology and mass rearing of Eucanthecona furcellata Wolf, a polyphagous predator, was studied under laboratory conditions. The predator has a total life cycle (egg to adult) of 46.25 days. The egg hatched 6 days after laying. The nymphs undergo seven instars with each stage ranging from 2.0 ‑ 2.35 days. Mass‑rearing techniques, effect of field releases and other ecological factors on pest population as well as other biological informations are also described.